Telling the Wave Function: An Electrical Analogy - Leonardo Chiatti (Foundations, 2022)
The double nature of material particles, i.e., their wave and corpuscular characteristics, is usually considered incomprehensible, as it cannot be represented visually. It is proposed to the student, in introductory courses, as a fact justified by quantum interference experiments for which, however, no further analysis is possible. On this note, we propose a description of the wave function in terms of a simple electrical analogy, which reproduces at least some of its essential properties. Our aim is to provide a cognitive representation of an analogical type: starting from a classical context (electrical circuits) and introducing in an appropriate way the notions of “wave” and “particle”, we show how typically quantum properties such as delocalization and entanglement emerge in a natural, understandable, and intuitive way.